(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
This article examines the development of comparative literature in Uzbekistan, emphasizing the growing role of translation and cross-cultural analysis. Particular attention is paid to Alisher Navoi’s treatise "Muhokamat ul-lugatayn" ("Judgment on Two Languages"), which is analyzed from a comparative methodological perspective. The study applies historical, epistemological, logical-methodological, and spiritual-ideological criteria to evaluate Navoi’s comparative analysis of Turkic and Persian literary traditions